Students’ Economic Backgrounds in Meeting Living Costs of Higher Education: A Regression Analysis - Ozekicioglu, Seda (International Journal of Economics and Financial Issues, 2017)
Economic backgrounds of students whom demand the higher education service can become a significant criterion regarding accessibility and continuity of the service. Higher education student costs consisting of tuition and living costs can be redeemed by some education aids provided either by governments or private sector for students from a low income group and/or that are successful. In this paper, an empirical study on the effects of economic status of higher education student on bearing their living costs and its results are evaluated. According to the results obtained by testing the model, increase in family income, which is an independent variable, decreases the possibility of difficulty in bearing living costs, while the other independent variables, which are increase in economic independence in housing method of the student and increase in difficulty in covering tuition fees, increase the possibility of difficulty in bearing living costs. Keywords: Living cost, economic factors, higher education, odds ratio JEL Classifications: H52, I22, I24